Tracing the threads of research to establish equitable and culturally appropriate pedagogical practices within mathematical interactions and discourse for all learners. Issue 1 (2nd January 2023) - Hunter, Roberta
ABSTRACT: Research by Wood and her colleagues has had a lasting and transformative impact on the mathematical outcomes for Pāsifika learners is Aotearoa/New Zealand. In this chapter, I describe a journey from what began as a solitary teacher searching for answers for their own discomfort at the inequitable outcomes for some students in her classroom to that of teacher educator and researcher. I describe the excitement of finding a myriad of studies by Wood and peers which opened doors to potential changes in pedagogical practices to better meet the needs of Pāsifika and Māori students. I outline the essence of these many studies and how they have been foundational for current 21st century mathematics classrooms. More importantly, I show how Wood and her fellow researcher's many theories have been extended in practical ways to be inclusive and build on the cultural and social world of Pāsifika and Māori students.